UJl HASIL KEPRASAN BEBERAPA VARlETAS TEBU LAHAN KERING PADA DAERAH BERIKLIM BASAH - , Purwono; Sugeng Sudiatso; Dwi Guntoro (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 1997)
The study of first rationed sugar cane on wet climate region was carried out at Sindangbarang Bogor (belong to type A according Schmidt and Fergusson classification) from October 1993 to April 1994. The study was designed to fined out the yield and total-sugar content. Several cultivar of Ps 87 (produced by P3GI) were tested (Ps 87-985, Ps 87-21718, Ps 87-22189, Ps 87-22704, Ps 87-21781, Ps 87-22098, Ps 87-21781, Ps 87-21067), and Ps 58 as a control. The result showed that the Ps 87-22074 produced the highest yield (19.524,7 g/m "juring") and total-sugar content (13,16%) among the other.